2016
DOI: 10.4049/jimmunol.1501835
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoproteins Are Critical for Pulmonary Innate Defense against Staphylococcus aureus Quorum Sensing

Abstract: Hyperlipidemia has been extensively studied in the context of atherosclerosis, whereas the potential health consequences of the opposite extreme, hypolipidemia, remain largely uninvestigated. Circulating lipoproteins are essential carriers of insoluble lipid molecules and are increasingly recognized as innate immune effectors. Importantly, severe hypolipidemia, which may occur with trauma or critical illness, is clinically associated with bacterial pneumonia. To test the hypothesis that circulating lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…Consistent with this, spontaneous triclosan-resistant fatty acid auxotrophs have previously been isolated from clinical samples (24). Previous studies focused on the interactions between S. aureus and lipoprotein particles showed that LDLs defended against S. aureus infection by sequestering autoinducing peptide and phenol-soluble modulins (40)(41)(42)(43)70). Our studies expand on these findings by demonstrating that S. aureus is also capable of utilizing LDLs as a source of fatty acids.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with this, spontaneous triclosan-resistant fatty acid auxotrophs have previously been isolated from clinical samples (24). Previous studies focused on the interactions between S. aureus and lipoprotein particles showed that LDLs defended against S. aureus infection by sequestering autoinducing peptide and phenol-soluble modulins (40)(41)(42)(43)70). Our studies expand on these findings by demonstrating that S. aureus is also capable of utilizing LDLs as a source of fatty acids.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, expression of secreted lipases is a clinically defining feature of S. aureus, and most strains encode multiple lipases (37,38). Previous studies established that LDL particles bind to and sequester factors secreted by S. aureus, such as autoinducing peptides and alpha-toxin (39)(40)(41)(42)(43), but the capacity of LDLs to serve as an exogenous source of fatty acids for S. aureus has not been explored.…”
mentioning
confidence: 99%
“…Consistent with the generality of this mechanism, it was recently reported that apolipoprotein B100 in VLDL and apoB48 in chylomicrons also inhibit quorum sensing by AIP sequestration (37). Most recently, it was found that mice with hypolipidemia that reduced ApoB levels in their lungs suffered from increased morbidity and inflammation in an S. aureus pneumonia model (38), highlighting the importance of sequestration of AIP by serum lipoproteins as a mechanism of innate immunity. In a separate study, James et al (34) discovered that AgrC point mutations that render AgrC constitutively active overcame quorum-sensing inhibition by serum lipoproteins, leading them to conclude that "sequestration of the AIP is likely to be the only mechanism by which the host innate immune response limits agr expression at the transcriptional level."…”
Section: Direct Action Of Serum and Ros On Agr Componentsmentioning
confidence: 71%
“…5c ). Furthermore, ApoB has been shown to contribute to the host defense against S. aureus in experimental models of skin 42 and respiratory 43 infection by antagonizing the agr quorum sensing system of S. aureus . To validate this hypothesis, A/J and C57BL/6 mice were treated with 4-aminopyrazolopyrimidine (4-APP), a drug that impairs low-density lipoprotein secretion 44 , and subsequently infected intravenously with S. aureus.…”
Section: Resultsmentioning
confidence: 99%